Georg Simmel – Norbert Elias – Alfred Sohn-Rethel - Aldo Haesler (Recherches Germaniques)
The relation between two of the most prominent 20th century thinkers to have reflected extensively on money, Georg Simmel and Alfred Sohn-Rethel, has not yet been sufficiently examined in the literature. Yet their common proximity to Kant is obvious, and both intended to bolster Marx’s theory by providing it with an epistemological framework. Whereas Simmel aimed to “re-Kantianize” Marx, however, Sohn-Rethel’s objective was to “Marxify” Kant. The aim of this article is not primarily to examine this astonishing symmetry, but rather to reformulate Kant’s categorical theory with relational categories that could be used as a foundation for a future relational sociology. It will do so, moreover, by making use of the work of Norbert Elias, which can mediate between these respective views.